INTERNATIONAL COOPERATION IN UZBEK CLASSICAL MUSIC IN RECENT YEARS (Web of Teachers: Inderscience Research, 2024)
In this article, information about the genres inherited from Uzbek music, their types is presented. Folk and professional genres in Uzbek music are interpreted.